PENERAPAN PENDEKATAN KEADILAN RESTORASI UNTUK MENCEGAH PERCERAIAN DI NAGARI SARUASO - Aldi Andryan; Khairina Khairina; Roni Efendi (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The main problem of this research is the application of the restoration justice approach to prevent divorce in Nagari Saruaso. The data obtained shows that from 2020-2022 there were 162 divorce cases in Nagari Saruaso, this is a cause for concern. So it takes thought and solutions to anticipate it. So this study aims to provide an alternative to restoring household relations through a Restorative Justice approach to prevent divorce. This type of research is Juridical Sociology with Qualitative Typology, where data obtained from the field is narrated, interpreted to provide answers to the research object. Primary data sources are ninik mamak, religious scholars, cadiak pandai, bundo kanduang and the wali nagari government. Secondary data sources from books, journals, and laws and documents from Wali Nagari. The results of the study revealed, firstly, based on efforts to apply the restoration justice approach to prevent divorce in Nagari Saruaso, it was carried out by involving all components into one forum, namely the involvement of ninik mamak, religious scholars, cadiak pandai and bundo kanduang to provide advice so that divorce does not occur and spouses husband and wife back in harmony. That the concept of applying the Restorative Justice approach is carried out by all the above components through Gondang Sayak and Gondang Kuali to prevent Divorce in Nagari Saruaso. Gondang Sayak is a peace process that only involves the closest family, then Gondang Kuali is an effort to reconcile husband and wife by involving all components such as ninik mamak, pious scholars, cadak smart, bundo kanduang. Second, the obstacles in applying the restoration justice approach based on the research results are several factors, namely; economic factors, educational factors, modernization factors, Domestic Violence (KDRT) factors